Large Language Models in Labor Market Research Data Management : Potentials and Limitations - Dörpinghaus, Jens [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2025)
"This contribution explores the application of large language models (LLMs) in labour market research data management, particularly in occupational data analysis. Based on our empirical studies of the automated classification of job titles and critical evaluations of AI-assisted text interpretation, we contend that, although LLMs present promising opportunities to improve research processes, such as providing query assistance, offering annotation support, and facilitating preliminary content structuring, they are inadequate for consistent data management, reliable analysis, and interpretative depth. Our findings suggest that, while LLMs can support research workflows as interactive tools, they cannot replace methodological approaches in data-driven social science research. Our aim is to contribute to the discussion on the scope and boundaries of LLM-based tools in research data management." (Authors' abstract, BIBB-Doku)
Keywords: S 6 Berufsbereiche; G 2.2.1 Technologisierung; T 3 Forschungsmethoden; 370; 300; Arbeitsmarktforschung; Berufsforschung; Forschungsdaten; Datenmanagement; Berufsklassifikation; Datenanalyse; Textanalyse; Automatisierung; Künstliche Intelligenz; Large Language Model